2016
DOI: 10.1002/j.1681-4835.2016.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining ‘Irrationalities’ of IT‐Enabled Change in a Developing Country Bureaucracy: The Case of Ghana's Tradenet

Abstract: Through a case study of Ghana's TradeNet, a business-to-government (B2G) Electronic Data Interchange (EDI) implemented to automate and integrate customs clearance, this article investigates 'irrationalities' of IT-enabled change in the context of a developing country bureaucracy. Our data revealed that despite TradeNet's potential for full automation and integration, bureaucrats sometimes preferred manual, face-to-face, paper-based practices. We explain such outcome-often depicted in the literature as a kind o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The study found some limitations to the full deployment of e‐government in the study organizations that were mainly issues of the capacity of target users, low resident awareness of e‐government tools at the MMDAs, financial inefficiencies, and the related infrastructural deficits. These limitations had also been identified by other studies (Addo, ; Alemna & Sam, ; Osei‐Kojo, ). This finding is in sync with the 2016 E‐Government Survey, which suggests that a major setback with Ghana's e‐government development is the lack of supporting infrastructure (United Nations, ).…”
Section: Discussion Of Findingsmentioning
confidence: 66%
See 1 more Smart Citation
“…The study found some limitations to the full deployment of e‐government in the study organizations that were mainly issues of the capacity of target users, low resident awareness of e‐government tools at the MMDAs, financial inefficiencies, and the related infrastructural deficits. These limitations had also been identified by other studies (Addo, ; Alemna & Sam, ; Osei‐Kojo, ). This finding is in sync with the 2016 E‐Government Survey, which suggests that a major setback with Ghana's e‐government development is the lack of supporting infrastructure (United Nations, ).…”
Section: Discussion Of Findingsmentioning
confidence: 66%
“…Issues such as the availability of ICTs, electricity, illiteracy, and telecommunications were raised as barriers to e‐government adoption in rural areas in Ghana. Other studies have explored the nature of adoption of e‐government, benefits, and challenges associated with its implementation in some selected government agencies, all excluding local government structures like MMDAs (Addo, ; Osei‐Kojo, ). Findings of these studies come to the consensus that e‐government has tremendous potential for making government institutions more efficient in the execution of their mandate (Alemna & Sam, ; Fiankor & Akussah, ; Misuraca, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two other logics have been identified in health-management ISs-the network and hierarchical-bureaucratic logics-and the formal logic embedded in network technologies disrupts and challenges the existing logic [54]. In a similar vein, the bureaucratic logic and managerialism logic have been found in trade-related ISs in Ghana, where the tensions and contradictions between the two logics were found to have enabled change in the bureaucracy [55].…”
Section: Interplays Between Institutional Logicsmentioning
confidence: 93%
“…Other developing countries such as Ghana and Mauritius that subsequently adopted Singapore's TRADENET as a best practice (De Wulf, 2005) have not had underpinning anticorruption strategies as ambitious or encompassing as Singapore's. In Ghana's case, TRADENET was implemented within a remit of improving efficiencies in trade clearance but despite the potential of the technology, corruption continued to persist and co-exist alongside other improvements within customs and the ports (Addo, 2016;Addo & Senyo, 2020). Table 5 summarizes motivations underpinning digitalization and corruption in the literature.…”
Section: Anti-corruption Strategymentioning
confidence: 99%
“…Table 5 summarizes motivations underpinning digitalization and corruption in the literature. (Addo, 2016;Amankwah-sarfo, Boateng, & Effah, 2018;Kock & Gaskins, 2013;Senyo, Liu, & Effah, 2019b), or be tactical i.e., have short-term expectations derived from a general belief in the potential of digital technologies to transform organization (Stremlau, Fantini, & Gagliardone, 2015).…”
Section: Anti-corruption Strategymentioning
confidence: 99%